2014
DOI: 10.1111/jeb.12361
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA as a tool for reconstructing past life‐history traits in mammals

Abstract: Reconstructing the ancestral characteristics of species is a major goal in evolutionary and comparative biology. Unfortunately, fossils are not always available and sufficiently informative, and phylogenetic methods based on models of character evolution can be unsatisfactory. Genomic data offer a new opportunity to estimate ancestral character states, through (i) the correlation between DNA evolutionary processes and species life-history traits and (ii) available reliable methods for ancestral sequence infere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
0
16
1
1
Order By: Relevance
“…Branch lengths are proportional to time. To confirm our results, analyses were repeated with Agnarsson and May‐Collado’s () phylogeny of 266 species of Cetartiodactyla based on cytochrome b sequence data and using the recent Figuet et al's () phylogenetic tree reconstructed from complete mitochondrial genome of 201 species of Cetartiodactyla. In all cases, results were qualitatively similar and we only present in this study those obtained with the phylogenetic supertree of mammalian species (Bininda‐Emonds et al.…”
Section: Methodsmentioning
confidence: 60%
“…Branch lengths are proportional to time. To confirm our results, analyses were repeated with Agnarsson and May‐Collado’s () phylogeny of 266 species of Cetartiodactyla based on cytochrome b sequence data and using the recent Figuet et al's () phylogenetic tree reconstructed from complete mitochondrial genome of 201 species of Cetartiodactyla. In all cases, results were qualitatively similar and we only present in this study those obtained with the phylogenetic supertree of mammalian species (Bininda‐Emonds et al.…”
Section: Methodsmentioning
confidence: 60%
“…Corroborating the existence of small-sized ancestral cetartiodactyls based on a sample of large-sized extant species would be quite reassuring regarding the reliability of these approaches. An analysis 6 130 135 140 145 150 of complete mitochondrial genomes in 201 species of cetartiodactyls suggested that DNA-aided reconstruction can estimate ancestral LHTs more accurately than classical methods (Figuet et al 2014). Mitochondrial DNA, however, is limited in size.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we generated a dataset of thousands of genes in 41 species, of which 22 were newly sequenced, and conducted analyses inspired by Romiguier et al (2013) and Lartillot and Delsuc (2012). Firstly, we approached ancestral body mass, longevity and age of sexual maturity based on the observed correlation between life-history and molecular traits across extant species (Romiguier et al 2013;Figuet et al 2014). Secondly, we 165 used the integrated approach developed by Lartillot and Poujol (2011), in which the correlated evolution of life-history traits and molecular parameters across the phylogenetic tree is modelled as a multivariate Brownian motion, so as to obtain quantitative estimates of ancestral body masses and credibility intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical data were gathered from several previous studies: a placental nuclear dataset of 16 concatenated genes in 73 taxa (Lartillot and Delsuc, 2012), another placental nuclear dataset of 180 concatenated exons from 33 placental taxa (Lartillot, 2013b;Ranwez et al, 2007), a mitochondrial dataset obtained by concatenating the 13 mitochondrial protein-coding genes from 273 placental mammals (Nabholz et al, 2013), another similar concatenation restricted to 201 Cetartiodactylia (Figuet et al, 2014) and an alignment of ribosomal RNA sequences (only the stem regions) from 33 Archaea and an outgroup of 12 Eubacteria (Groussin and Gouy, 2011). In each case, the tree topology was obtained from the corresponding publication and was used in all subsequent analyses.…”
Section: Data and Simulationsmentioning
confidence: 99%